Penggunaan Berbagai Tipe Habitat oleh Burung di Kampus Institut Pertanian Bogor, Darmaga, Bogor, Jawa Barat - Yeni A. Mulyani; Maria Ulfah; Sutopo . (Media Konservasi, 2013)
This study examined bird diversity in isolated and fragmented habitats in IPB Darmaga Campus, Bogor, West Java Indonesia. Bird surveys were conducted in plots of several habitat types using MacKinnon List and point count methods. A total of 52 bird species were recorded during the study. Use of habitats by several breeding birds, such as Red-breasted Parakeet Psittacula alexandri indicated the importance of habitats for the survival of bird community in the area. Monitoring of population, especially those of breeding species, is necessary to assess the suitability of the area as wildlife refuge and to make necessary management recommendation. Keywords: bird, isolated, fragmented, habitat use, population